2019
DOI: 10.1186/s12883-019-1543-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive mediated eye movements during the SDMT reveal the challenges with processing speed faced by people with MS

Abstract: BackgroundThe Symbol Digit Modalities Test (SDMT) is regarded as the cognitive test of choice for people with MS (pwMS). While deficits are linked to impaired processing speed, the mechanisms by which they arise are unclear. Cognitive-mediated eye movements offer one putative explanation. The objective of this study was to determine the association between eye movements and performance on the SDMT.MethodsThirty-three people with confirmed MS and 25 matched healthy control subjects (HC) were administered the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
7
2
Order By: Relevance
“…In a study by Huijbregts et al, 42 found that RRMS were more vulnerable on tasks that concurrently place demands on processing speed and visual-spatial working memory, such as the OM n-back. Interestingly, in our study, we did not see a commensurate reduction in performance on the SDMT, the proposed gold standard measure 27,43 that similarly places demands on visual WMem and processing speed 44,45 ; indeed all pwMS identi ed as impaired by the SDMT were also identi ed by the OM n-back. This is in line with previous studies that have similarly found that the SDMT's ability to detect cognitive deterioration within 2-3 years is poor 46,47 , with performance estimated to decrease by only .22 decrease per year 48 .…”
Section: Discussioncontrasting
confidence: 69%
“…In a study by Huijbregts et al, 42 found that RRMS were more vulnerable on tasks that concurrently place demands on processing speed and visual-spatial working memory, such as the OM n-back. Interestingly, in our study, we did not see a commensurate reduction in performance on the SDMT, the proposed gold standard measure 27,43 that similarly places demands on visual WMem and processing speed 44,45 ; indeed all pwMS identi ed as impaired by the SDMT were also identi ed by the OM n-back. This is in line with previous studies that have similarly found that the SDMT's ability to detect cognitive deterioration within 2-3 years is poor 46,47 , with performance estimated to decrease by only .22 decrease per year 48 .…”
Section: Discussioncontrasting
confidence: 69%
“…It is not surprising that there is a correlation between the SDMT and eye-tracking, as the SDMT assesses visual scanning, memory and perceptual speed, among other functions ( 26 ). Pavisian et al demonstrated that the eye-tracking behavior of MS patients differs from that of healthy individuals during the performance of the SDMT ( 9 ). We extend these findings to a more naturalistic task that is directly linked to the patients' daily lives and stress the importance of intact information processing speed for visual search in the context of real-life situations.…”
Section: Discussionmentioning
confidence: 99%
“…This decision is driven by visuospatial attention and modulates the speed of visual search (13). In general, attentional top-down control is one of the key aspects in visual search (14) and thus eye-tracking can reflect cognitive processes (7,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations